Bullous Wells' syndrome - Bengu Cevirgen Cemil; Necip Enis Kaya; Aysun Gokce; Muzeyyen Gonul (Our Dermatology Online, 2016)
Wells' syndrome (WS) is an uncommon inflammatory skin disease which typically presents single or multiple erythematous and edematous urticarial plaques similar to cellulitis. The lesions may evolve into blue-grey morphea-like lesions and may persist for weeks or months. They ultimately heal without scar. Other clinical presentations reported in literature include papular and nodular and, rarely, bullous eruptions. Previously, bullous Wells' syndrome was rarely reported in the literature. Herein, we describe a case of a female patient with bullous Wells' syndrome localized to the upper limbs without any associated disorders.